O efeito contingencial da estratégia de negócio e da incerteza ambiental na relação entre a estrutura organizacional e a implementação da estratégia - Vargas, Eduardo (Universidade do Vale do Rio dos Sinos, 2015)
Studies on implementation of the strategy given its importance for the company to achieve competitive advantage are increasing. However, there is a need to understand with more depth the requirements for the successful implementation of the strategy in retail. There is room in the literature in the field of retail strategy to better understand the relationship between structure, implementation, and organizational performance in this sector. The literature of the strategy area features several studies that examine the relationship between organizational structure and implementation. There are however ways to understand this relationship, one refers to dimensions that can moderate this relationship. This study goes into this theoretical discussion, analyzing the influence of business strategy and environmental uncertainty moderating the relationship between organizational structure and strategy implementation. In addition, this study aims to understand how these relations are manifested in the power retail environment outside the home. In this sense, this research through a survey of the cut cross-sectional empirically evaluates the contingent effect of business strategy on the relationship between organizational structure and implementation of the marketing strategy. For this, they considered 171 questionnaires collected from small businesses in the retail sector of food outside the home. The survey results showed that the decentralization of the organizational structure positively influence the implementation of the strategy, as it was confirmed that the formalization negatively influences the implementation of the strategy. Furthermore, the results indicate that the business strategy moderates the relationship between structure and implementation.
Keywords: Implementação da estratégia; Estrutura organizacional; Estratégia de negócio; Incerteza ambiental; Desempenho; Strategy implementation; Organizational structure; Business strategy; Environmental uncertainty; Performance; ACCNPQ::Ciências Sociais Aplicadas::Administração